Upgrading an intronic TMEM67 variant of unknown significance to likely pathogenic through RNA studies and community data sharing. (21st October 2022) - Kurolap, Alina; Mory, Adi; Simchoni, Sharon; Krajden Haratz, Karina; Malinger, Gustavo; Birnbaum, Roee; Baris Feldman, Hagit; Yaron, Yuval
Abstract: Fetal phenotype: A couple of Ashkenazi Jewish descent was referred for an early anatomy scan at 14 + 2 weeks of gestation following a previous pregnancy termination due to posterior encephalocele and enlarged kidneys. The index pregnancy was also positive for several fetal abnormalities, including enlarged kidneys with cystic dysplasia and abnormal cerebellar morphology highly suggestive of Joubert syndrome. Genetic diagnostic test performed, result, and interpretation: Trio exome sequencing revealed compound heterozygosity for variants in the TMEM67 gene: a known pathogenic maternally inherited variant found in trans with a paternal intronic variant of unknown significance. RNA analysis revealed that the intronic variant creates a cryptic acceptor splice site in intron 12, leading to the insertion of 22 bp and causing a frameshift with a premature stop codon. This analysis enabled the reclassification of the intronic variant to likely pathogenic . Implications and novelty: This information empowered the couple to make informed reproductive choices and opt for preimplantation genetic testing (PGT) for future pregnancies. Key points: What's already known about this topic? Intronic variants are often classified as variants of unclear significance (VUS). What does this study add? This report highlights the importance of RNA analysis in cases where an intronic VUS is found in trans with a pathogenic or likely pathogenic variant in an autosomal recessive gene compatible with the fetal phenotype.